A Cast Study to Investigate an Affordable Cloud-based Server for Worksharing to Benefit Academia & Small Businesses (International Journal of Scientific Research and Management (IJSRM), 2021)
Real-time collaboration of multiple digital models is vital for successful construction projects using Virtual Design and Construction (VDC) or Building Information Modeling (BIM). Real-time collaboration allows users to workshare within a multidisciplinary team to co-author multiple smart digital models for better efficiency. This can be done in two ways, either using a physical server (Local Area Network/LAN server) or cloud-based server (Wide Area Network/WAN server). Such cloud-based servers are A360, C4R, Collaboration for Revit, or BIM360Design collaborate, etc. However, above-mentioned cloud services come at a significant price, making it challenging for academia and small businesses to perform real-time collaboration using BIM/VDC models. To find an affordable alternative, an attempt was made as part of the Virtual Design and Construction (VDC) course offered by the Construction Science and Management Department (CSM). For this case study, a popular and free (Google) cloud server was tested as a WAN server to host four multidisciplinary collaborative VDC central models for five users across five different geographic locations and time zones. The study rendered successful results to establish a real-time collaborative workshare environment; hence, can significantly benefit academia and small business.